Analysis of Akhlak Values in Science Textbooks for Madrasah Aliyah - Nurlela, Andi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
Integrating akhlak values ​with all subjects at all levels of education is one of the keys to forming students with a religious character. So that science and religion are no longer separated. Including at the Madrasah Aliyah (MA) education level, Islamic-based schools, but in reality, it is still difficult not to separate science and religion, especially in science subjects. Therefore, this study aims to analyze religious values, especially in the akhlak aspect in science textbooks for 10th grade Madrasah Aliyah (MA), and how students internalize these religious values. This research uses a qualitative descriptive approach, specifically content analysis. The results of this study indicate that the learning materials in science textbooks for 10th at Madrasah Aliyah (MA) contain akhlak values, including akhlak to Allah SWT, akhlak to fellow human beings, and akhlak to the environment. The media used to internalize akhlak values ​​in science learning is manufacturing printed and electronic teaching materials so students can easily access and understand them.